Carboxylic multi-walled carbon nanotubes as immobilized stationary phase in capillary electrochromatography - Sombra, Lorena Luján (2008)
Carboxylic multi-walled carbon nanotubes (c-MWNT) have been immobilized into a fused-silica capillary for capillary electrochromatography. The c-MWNT were successfully incorporated after the silanization and coupling with glutaraldehyde on the inner surface of the capillary. The electrochromatographic features of the c-MWNT immobilized stationary phase have been evaluated for the analysis of different compounds of pharmaceutical interest. The results indicated high electrochromatographic resolution, good capillary efficiency and retention factors. In addition, highly reproducible results between runs, days and capillaries were obtained.